Adefovir accumulation in the renal interstitium triggers mast cell degranulation and promotes renal interstitial fibrosis. (15th April 2022) - Zhou, Yan; Wei, Mengmeng; Zhang, Mingkang; Zhang, Jianping; Tang, Fabing; Wu, Xin'an
Graphical abstract: Highlights: Adefovir accumulated in the renal interstitium causes renal interstitial fibrosis when Oat1/3 were inhibited by probenecid for long-term. Adefovir accumulation in the renal interstitium triggers mast cell degranulation and promotes renal interstitial fibrosis. Mast cell membrane stabilizer sodium cromoglycate and angiotensin receptor antagonist valsartan ameliorate adefovir-associated fibrosis. Abstract: Organic anion transporters 1 (OAT1) and OAT3 are responsible for transporting adefovir (ADV) into renal tubular epithelial cells. Our previous research found that ADV accumulated in the renal interstitium and caused renal interstitial fibrosis when Oat1/3 were inhibited by OATs inhibitor probenecid for long-term. Mast cells (MCs) in the interstitial space are considered to be key drivers of renal fibrosis. The current work investigated the effect of ADV on MCs in vitro and during the development of interstitial fibrosis in rats. Results indicate that ADV triggers chymase release from cultured RBL-2H3 mast cells in a time-and concentration-dependent manner. Angiotensin II (Ang II) in renal interstitium is generated mainly by chymase, renin and other products released from MCs, and has a direct effect on fibrosis through the angiotensin receptor. The concentrations of Ang II and fibrosis was significantly increased after administration of ADV alone or with probenecid for 4 weeks. The MCs membrane stabilizer sodium cromoglycate (SCG) and the angiotensin receptor antagonist Valsartan (VAL) could ameliorate ADV-induced nephrotoxicity. Additionally, SCG or VAL could reduce the accumulation of ADV in the renal interstitium by upregulating the expression of Oat1/3 and multidrug resistance-associated protein 4. Therefore, ADV accumulation in the renal interstitium could promote the degranulation of interstitial MCs and drive the development of renal fibrosis. SCG or VAL could ameliorate ADV-associated fibrosis by decreasing degranulation of MCs and accelerating renal clearance of ADV.